PENGEMBANGAN ELECTRONIC HANDOUT RAGAM MARINE FUNGI SEBAGAI PENUNJANG MATERI KEANEKARAGAMAN HAYATI DI SMA - Aida Dwi Agnes Andriani; Aulia Ajizah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the diversity of microscopic fungal colonies in seawater and to determine the validity, readability and response of students to the Electronic Handout of various Marine Fungi. The study began with descriptive research to determine the needs of students and teachers. The research was conducted by taking seawater samples to then be planted in PDA culture media. Colony growth data was used as material to be included in the developed Electronic Handout. The development of the Electronic Handout used a 4-D model. The Electronic Handout design was validated by material experts and media experts. If the Electronic Handout is valid and feasible to use, then a readability test is carried out on a small group of students to see the effectiveness of the developed Electronic Handout, then it is implemented in class XI of the 2024/2025 academic year at SMAN 7 Banjarmasin. Based on the results of microscopic fungal cultures from seawater samples, it shows that there are three fungal colonies. The results of the development of the Electronic Handout show material validity of 86.64% (very valid) and media validation of 97% (very valid) so that it is feasible for digitization, the readability of the Electronic Handout is 88.8% (very good) and the student response is 89.16% (very interesting). In conclusion, the isolation of microscopic fungi from seawater samples succeeded in obtaining three colonies, and the developed Electronic Handout was declared very valid, feasible for digitization, easy to read, and received a positive response from students.